O vício em pornografia : relações com a adicção na atualidade - Baldim, Fernanda Alves (2017)
The objective of the research consisted on a study of pornography and the relation with its actual addiction. Thereunto, it was analyzed thirty-four internet written testimonies posted by people in a specialized forum destined to help people break-off with the addiction. The subjects of the testimonies had presented themselves as male, with the age between seventeen and forty years old. It sought to do a research that explain, problematize and understand the pornography addiction. Subjects those suffer because of the addiction relate the studied phenomenon with the frequent and exclusive use of pornography. These studied situations where the subjects turn themselves to the virtual world, place of worldwide exposition, to find some sort help for the matters which consequences generally drives them to isolation and brake ties with social relations. For the development of the research, the researcher used Roque Moraes' method of contentment analyses. Through the reading and rereading of the thirty-four posted testimonies, it was possible to divide them in six categories: Silent Triggers - from magazines to internet; Shame - guilty and masturbation; Fetish and Phantasy; The Addiction and its Symptoms - the degradation spiral; The (In)capability of Love; The Asking for Help. Psychoanalytic Theory based the fundaments of the analyses and interpretations. From the testimonies, the hypothesis psych economy related with the pornography addiction presented itself as a mean of reduction of unpleasant feelings and tense promoting situations. It considered that the uncontrollable search for pleasure by primitive chemical reactions resulted in self-destructive movements. Ergo, the pornography addiction understanding as a non-neurotic psych mean of manifestation and the recognition of the suffering generated by this addiction is from narcissist order, it menaces the egoic integrity of the addicts and goes against the purpose of Eros: the union of pares.